THE EFFECTIVENESS OF USING SCRABBLE GAME IN MASTERING ENGLISH VOCABULARY - Fitriya Fitriya; Maskhurin Fajarina (Journal of Student Research, 2023)
This research aims to determine the effectiveness of using scrabble game in students’ vocabulary mastery in seventh grade of junior high school. The study was carried out at SMPN 1 Gudo Jombang. Pre-experimental research techniques and a quantitative research design were used in this study. A one-group pretest-posttest design was adopted by the researcher. Thirty students from class VII-H of SMPN 1 Gudo made up the sample for this study. Tests were utilized by the researcher to gather data. The findings of this study suggest that playing scrabble can help students learn more vocabulary. The significant value obtained from the data analysis utilizing the paired sample t-test and normality test in SPSS version 25 statistics supports this. From normality test a significance result of 0.106 > 0.05, indicating that the data are normal. The paired sample t-test additionally displays a significance value of 0.000 0.05, indicating that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. Given that the scrabble game has a considerable impact on students' vocabulary knowledge, it is advised that it be used to help students learn vocabulary.